Information management the evaluation of information systems investments - Willcocks, Leslie (Chapman & Hall, 1994)
This book provides a practical insight to the techniques used in assessing the impact of information technology in your business, before you make a strategic purchase. This book is a guide to recent management research and best practice in industry today. It provides analyses, and measures profit from IT expenditure in companies today. It is divided into four parts: the first two chapters are an overview of the area; the second analyzes the strategic dimension, the third looks at the techniques of evaluation in information systems investment; and the final part looks at the processes and new techniques in the management of information systems investment.